The hydrocarbon source rocks of the Pliensbachian (Early Jurassic) in the Asturian Basin (Northern Spain): Their relationship with the palaeoclimatic oscillations and gamma-ray response. - Gómez, Juan José; Comas-Rengifo, M.J.; Goy, A. (Journal of Iberian Geology, 2016)
Deposition of black shale facies, one of the main contributors for hydrocarbon production, is commonly assumed to be linked to Oceanic Anoxic Events (OAEs), which are supposed to be generated during warm palaeoclimats. This assumption could bias the exploration for hydrocarbon source rocks preferentially towards sediments deposited under warm palaoenvironments, as a preferential guide for hydrocarbon exploration. As a consequence, the establishment of the links between palaeotemperature and the formation of organic-rich deposits is of primary importance to find arguments on this subject. For this purpose, the Upper Sinemurian, Pliensbachian and Lower Toarcian (Lower Jurassic) deposits of the Asturian Basin in Northern Spain, including more than 100 m thick succession containing organic-rich and black shale deposits, has been studied. Correlation between palaeoclimatic data, previously obtained from oxygen isotopes, and the TOC content reveals that black shales and organic-rich sediments were deposited not only during warming intervals but also during a prominent cooling event that occurred at the Late Pliensbachian. This cooling interval has been pointed out as one of the main candidates to have developed ice caps in the poles during the Jurassic. On the contrary, no black shales were generated during the postulated Early Toarcian OAE, which coincides with a superwarming interval. Additionally, the study of the facies cycles and the measurement of gamma-ray in outcrops and its correlation with TOC content provides data on the use of natural radioactivity and sea level changes as a proxy for preliminary organic matter richness evaluation.